Termohidravlična analiza obratovanja uparjalnika za ukapljeni naftni plin - Bašič, Sani (Strojniški vestnik, 2003)
This paper deals with the thermohydraulic characteristic of an electrical liquefied-petroleum-gas (LPG) revaporizer. To begin with both the revaporizer's description and its working performances are presented. The main goals of the analysis are defined and the quasi-axisymmetrical revaporizer section is introduced. The governing equations for Newtonian fluid flow in the region of the secondary liquid and for flow through a porous heater are presented. The boundary conditions on the computational region boundaries are prescribed. Further basic empirical corelations for the evolution of the transport phenomena within the individual revaporizer zones are presented. Special attention is devoted to the convective boiling process of the binary mixture in helicaly coiled tubes. The iterative calculating procedure with which we finally reached the working state of the device is explained. At the end the achieved results are discussed with comments and conclusions included.The operating point of the revaporizer was to lie inside the prescribed temperature range for the selected combination of process parameters.
Keywords: prenos toplote; uparjalniki; analize termohidravlične; plini naftni ukapljeni